The warrior, military ethics and contemporary warfare Achilles goes asymmetrical - Kaurin, Pauline M. (Military and defence ethics series, 2014)
When it comes to thinking about war and warriors, first there was Achilles, and then the rest followed. The choice of the term warrior is an important one for this discussion. While there has been extensive discussion on what counts as military professionalism, that is what makes a soldier, sailor or other military personnel a professional, the warrior archetype (varied for the various roles and service branches) still holds sway in the military self-conception, rooted as it is in the more existential notions of war, honor and meaning. In this volume, Kaurin uses Achilles as a touch stone for discussing the warrior, military ethics and the aspects of contemporary warfare that go by the name of 'asymmetrical war'. The title of the book cuts two ways - Achilles as a warrior archetype to help us think through the moral implications and challenges posed by asymmetrical warfare, but also as an archetype of our adversaries to help us think about asymmetric opponents.